PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN BERKOMUNIKASI SISWA PADA MATERI PENCEMARAN LINGKUNGAN - Cahyeni, Rina; Suganda, Ondi; Lismaya, Lilis (Bioed : Jurnal Pendidikan Biologi, 2019)
The aim of this research is to analyze the application of Problem Based Learning (PBL) model to students' communication skills on environmental pollution material. The method used was Quasi-experimental with pretest-posttest control group design. The population is all students of class X and sampel used as many as 38 students in the experimental class and 38 students in a class taken control receipts Cluster random sampling technique. The instruments used in this research are description test, performance assessment, observation sheet and questionnaire. The results showed that the complete body of the stages of the model PBL and implemented in accordance with the order of the syntax of the learning model, so it can improve the communication skills of students is evident from the results of hypothesis testing showed the value of tcount > t table (4.61>2.65) then H 1 received. Where the average value obtained 82 posttest experimental class in the high category while the control class 68 including lower category, then taught using a model of PBL in the experimental class is better than classroom teaching model of control. This proved that the model of PBL affects the communication skills of students as a model of PBL as a whole engages students in the learning process from beginning to end. In addition, students responded positively to the application of this model.Â Keywords: Communication Skills, Problem Based Learning (PBL), EnvironmentalÂ  Pollution